2012
DOI: 10.1186/1475-2859-11-119
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Acetobacter sp. CCTCC M209061 for efficient asymmetric reduction of ketones and biocatalyst recycling

Abstract: BackgroundThe bacterium Acetobacter sp. CCTCC M209061 is a promising whole-cell biocatalyst with exclusive anti-Prelog stereoselectivity for the reduction of prochiral ketones that can be used to make valuable chiral alcohols such as (R)-4-(trimethylsilyl)-3-butyn-2-ol. Although it has promising catalytic properties, its stability and reusability are relatively poor compared to other biocatalysts. Hence, we explored various materials for immobilizing the active cells, in order to improve the operational stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
1
23
1
4
Order By: Relevance
“…Besides that, there were appearances of corrugation on the surface of the bead, as shown in Figure 2, which was similar to the previous observation of Chen et al (2012), which used scanning electron microscopy of Ca-alginate and alginate-chitosan beads containing Acetobacter cells (Chen et al, 2012).…”
Section: Scanning Electron Micrograph (Sem) Of Sodium Alginate Bead Isupporting
confidence: 87%
“…Besides that, there were appearances of corrugation on the surface of the bead, as shown in Figure 2, which was similar to the previous observation of Chen et al (2012), which used scanning electron microscopy of Ca-alginate and alginate-chitosan beads containing Acetobacter cells (Chen et al, 2012).…”
Section: Scanning Electron Micrograph (Sem) Of Sodium Alginate Bead Isupporting
confidence: 87%
“…29 For instance, uoxetine, which is used for the treatment of depression among others mental disorders, and (R)-benzyl-4-hydroxyl-2-pentynoate, which is a potential therapeutic for Alzheimer's disease, are synthesized from the chiral intermediate secondary alcohol (R)-4-(trimethylsilyl)-3-butyn-2-ol, respectively. 30,31 (R)-2-Octanol was proven to be a precursor compound for the several optically active pharmaceuticals products. 32 Isoproterenol, is a pharmaceutical drug which treats bradycardia, and neobenodine, which has antihistaminic and anticholinergic action, and both are obtained from chiral secondary alcohols.…”
Section: Production Of Secondary Alcoholsmentioning
confidence: 99%
“…20 Secondary alcohols are the most frequently used molecules in lipase-catalysed kinetic resolutions not only because of their importance in organic synthesis but also because lipases usually show much higher enantioselectivity in resolutions towards secondary alcohols than in those towards primary or tertiary alcohols. 31 In enzymatic kinetic resolutions of secondary alcohols, the outcome is normally highly predictable, and it follows Kazlauskas' rule. 40 Usually, the (R)-alcohol is converted into (R)-acetate at a higher rate than its antipode with high ee, leaving the (S)-alcohol as an enantiomerically pure unreacted enantiomer.…”
Section: Production Of Secondary Alcoholsmentioning
confidence: 99%
“…Alginates with concentration below 1.5% produced non spherical and very fragile beads [36][37], whereas 23% concentration of alginate produced spherical and strong beads [37]. A research by Kong et al [38] demonstrated that the alginate concentration above 4% caused a very viscous solution, so it was difficult to produce spherical beads.…”
Section: (1) 2018 3515-3528mentioning
confidence: 99%